Land Ownership and Its Rulings in the Qur’an and the Torah: A Comparative Study - Saleh, Alaa Dawoid Salman (International Conference on Islamic Studies, 2025)
This research explores the concept of land ownership as presented in two major holy scriptures: the Noble Qur'an and the Torah. The primary problem addressed in this study is the divergence and convergence of ownership rulings within these texts and their implications for understanding religious law. The objective is to clarify the rulings regarding land ownership in both scriptures and to assess the degree to which these rulings are applied by Jewish communities. To achieve this, the study employs a comparative analytical method, beginning with an introduction to the status of the holy books, followed by an examination of the concept of land ownership and its conditions in the Qur'an. It then investigates similar rulings in the Torah and evaluates the consistency of their practical application among Jews. The findings indicate that Islamic law on land ownership, as derived from the Qur'an, is comprehensive, just, and rooted in monotheism, whereas the Torah includes provisions that have undergone interpretation and alteration over time, leading to varying practices among Jewish followers. These results underscore the superiority and coherence of Islamic legislation in maintaining divine intent and justice. This study contributes to interfaith understanding by providing an informed comparative perspective on religious laws, reinforcing a Muslim's conviction in the integrity of Islamic teachings, and revealing deviations from divine law in other traditions. Ultimately, it highlights Islam’s unique position as a true religion grounded in Tawhid (monotheism) and sincere worship of Allah.